Efficacy of 2‐Mercaptoethane Sulfonate Sodium (MESNA) in the Prevention of Pancreatitis After Endoscopic Retrograde Cholangiopancreatography: A Randomized Open Label Trial - Amir Sadeghi; Hesamoddin Samar; Mohammad Abbasinazari; Parvaneh Mohammadi; Ali Abazarikia; Shadi Ziaie (JGH Open)
ABSTRACT Background and Aim Oxidative stress has been considered a factor in the development of post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP). The present clinical trial evaluated whether adding intravenous mesna to rectal indomethacin could prevent or alleviate PEP. Methods An open‐labeled clinical trial was done on 698 participants undergoing endoscopic retrograde cholangiopancreatography (ERCP). Eligible patients received 100 mg indomethacin suppository 30 min before undergoing ERCP. Randomly, the participants received 400 mg intravenous mesna or nothing 30 min before doing the procedure. The PEP incidence and degree were measured in the patients as the main outcome. Results The total rate of PEP was equal to 13.7%. No significant difference was seen in the rate and severity of PEP between the mesna plus indomethacin and indomethacin alone arms (14% vs. 13.4%, respectively, p = 0.671). In high‐risk patients, PEP rate and severity were lower in the mesna plus indomethacin group compared with indomethacin alone group and the statistical analysis showed that the difference was significant (41.7% vs. 51.8%, respectively, p = 0.033). Conclusion In high‐risk patients undergoing ERCP, a combination of intravenous mesna plus rectal indomethacin may decrease the PEP rate and severity.